(untitled) (Research, Society and Development, 2022)
Veterinarians are health professionals who are intensely dedicated to the animals under their care, performing long working hours and, sometimes, not having their work appreciated. The municipality of Santa Maria has a network of veterinary services composed by 2 hospitals, 25 clinics and a total of 722 professionals up to this date, working to prevent and maintain the health of animals. The objective of this study is to describe the profile of these workers and examine their feeling on professional valorization. For this purpose, a descriptive research was carried out via questionnaire applied online, between June and July of 2021. Veterinarians working directlty with patients in the municipality were subjects of the research. Among the 120 professionals evaluated, 72.5% were women, 48.3% were between 20 and 30 years old, 57.5% were single, 70.9% had worked directly with the patient for less than 10 years, 50% worked in a public hospital and 50% in private institutions or performing home care. Out of these professionals, 78.3% had only one employment relationship, 49.2% had a weekly workload of more than 41 hours and 33.3% saw more than 15 patients per week. There were many professionals with signs of job burnout. Of those interviewed, 70% did not feel appreciated as professionals and 94.2% considered that the veterinarian is not appreciated in Brazil, but 62.5% would not like to practice another profession, demonstrating satisfaction in performing veterinary medicine.